Charge Collection Dynamics of the ARCADIA Passive Pixel Arrays: Laser Characterization and TCAD Modeling - Corradino, Thomas; Dalla Betta, G.-F.; Neubüser, C.; Pancheri, L. (Frontiers in Physics, 2022)
Monolithic Active Pixel Sensors (MAPS) represent one of the most promising technologies for the next generation of radiation detectors. The ARCADIA project aims at the development of Fully Depleted (FD) MAPS employing a production process compatible with a 110nm commercial CMOS technology. The first engineering run of the project included matrices of active pixels with embedded analog and digital frontend electronics and passive test structures such as passive pixel arrays, MOS capacitors and backside diodes. Although the produced samples were already characterized from the electrical point of view, a thorough study of the charge collection dynamics of the passive pixel arrays was still missing. In this paper we show the results of the dynamic characterization of a group of passive pixel arrays with different pixel pitches (50, 25 and 10 micrometers) and different pixel layouts. The tested samples have been illuminated from the backside with an infrared and a red laser with wavelengths equal to 1060 nm and 660 nm, respectively. The pixel arrays have been mounted on a custom readout PCB connected to an external amplifier with 1 GHz bandwidth and the signals have been acquired through a fast digital oscilloscope. We employed both focused and unfocused laser spots to evaluate the change in the measured signal as a function of the laser spot position and the average response of the pixel arrays. An excellent agreement has been demonstrated by comparing the measured signals with the results of transient TCAD simulations and a time for 50% charge collection of 7.8, 4.2 and 2.6 ns has been predicted and experimentally validated in pixels with 50, 25 and 10 micrometers pitch, respectively.